2022
DOI: 10.1021/acs.orglett.2c02671
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Imide Synthesis through a Nitrile Ylide Formation/Trapping Cascade

Abstract: A visible-light-promoted three component reaction of diazo compounds, nitriles, and carboxylic acids is reported. The reaction utilizes acceptor-only diazo compounds as carbene precursors and nitriles as carbene-trapping reagents to form the key nitrile ylides. Under the optimal reaction conditions, a wide range of imide products were obtained in good to excellent yields. The gram-scale synthesis and synthetic application of the imide products to form isoquinoline-1,3(2H,4H)-dione derivatives further proved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…More recently, in 2022, Zhao, Li and co-authors (Scheme 12a), 31 and Xuan and co-authors (Scheme 12b) 32 have simultaneously and independently reported a remarkable blue light-mediated cascade reaction employing alkyl diazoacetates 35 in the presence of carboxylic acids 47 and nitriles 48 to afford the corresponding non-symmetrical imides 49 via a Mumm rearrangement (Scheme 12c).…”
Section: Acceptor-only Diazo Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in 2022, Zhao, Li and co-authors (Scheme 12a), 31 and Xuan and co-authors (Scheme 12b) 32 have simultaneously and independently reported a remarkable blue light-mediated cascade reaction employing alkyl diazoacetates 35 in the presence of carboxylic acids 47 and nitriles 48 to afford the corresponding non-symmetrical imides 49 via a Mumm rearrangement (Scheme 12c).…”
Section: Acceptor-only Diazo Compoundsmentioning
confidence: 99%
“…31 On the other hand, Xuan and co-authors have investigated additional classes of acceptor-only diazo compounds 2 , with EWG = CO 2 Et, CF 3 and P(O)(OEt) 2 , thus producing a total of 45 examples of imides 49 , in 37–97% yields (Scheme 12b). 32 The proposed mechanisms for these reactions start with the blue light-mediated photolysis of the acceptor-only diazo compound 2 , leading to the free carbene 52 , which is subsequently trapped by the nitrile 48 (used as solvent) to afford the nitrilium ion intermediate 53 . This compound can react either with carboxylic acid 47 or benzotriazole 50 as suitable nucleophiles to afford the corresponding adducts 55 or 51 , respectively.…”
Section: Acceptor-only Diazo Compoundsmentioning
confidence: 99%
“…g . aryldiazoacetates), [17a–h] aryl/aryl diazoalkanes, [17i–j] acceptor‐only diazoalkanes, [17k–l] as well as other types of diazo compounds (pyridotriazoles and cyclic diazoalkanes) were all suitable substrates to give carbene intermediates under sole visible light irradiation (Scheme 2). [17m–n] Among the photochemical cyclopropanation reactions reported, the aryldiazoacetates were the mostly investigated carbene precursors.…”
Section: Cyclopropanation By Photochemical Carbene Transformation Rea...mentioning
confidence: 99%
“…Is is known that the vast majority of reactions driven by visible light involve diazo compounds as precursors of carbenes . In contrast, there has been little progress in visible light-driven diazo compounds as precursors of radicals until recently .…”
mentioning
confidence: 99%